Next Generation Quantitative Genetics in Plants - Jiménez-Gómez, José M. (Frontiers in Plant Science, 2011)
The analysis of continuous phenotypic traits through quantitative trait loci analysis, or QTL analysis, allows identification of the loci responsible for the variation observed in nature. QTL analyses involve establishing associations between genetic markers and the phenotypic variation of a quantitative trait in a segregating population. The laborious task of acquiring genetic markers and phenotypes in segregating populations have continuously benefit from technical advances. The new high-throughput sequencing technologies, or HTS, are radically transforming the way QTL analyses are performed. These technologies have the ability of rapidly and inexpensively sequence billions of bases without previous knowledge of the genomes analyzed. The development of HTS has been accompanied by a rapid progress in experimental protocols, computational pipelines and statistical frameworks to fit researchers needs. Some of these advances allow detection of molecular markers and phenotypes with a resolution never achieved before. In this review I discuss the application of HTS in quantitative genetics, focusing on molecular marker discovery, population genotyping and expression profiling for eQTL analysis.